(untitled) (Acta Scientiarum. Technology, 2013)
In recent times, food and water laboratories have aimed to improve their processes to meet market demands. In order to contribute to the efficacy and development of these processes, new methods must be sought, among which is intra-laboratory quality control. This research study portrays the use of this method in a food and water laboratory, in order to analyze the intra-laboratory statistical control of chicken raw materials. To that end, the methodology applied was: Exploratory data analysis; Cochran´s test, to assess the homogeneity of variances; Dixon´s Test, to verify whether the means are part of the same distribution; calculation of repeatability and reproducibility; calculation of the uncertainty of the mean; Snedecor´s F method, to compare the variances; and Dixon´s test, to compare laboratory variances. The analysis parameter analyzed in the studied raw material was the proficiency of technicians with regard to the accuracy of analyses of total coliform count in the raw materials prior to chilling. The final results showed low data variation around the mean, as well as significant reliability of the obtained results. Â